2018
DOI: 10.22616/esrd.2018.123
|View full text |Cite
|
Sign up to set email alerts
|

Financial efficiency of the industry producing fodder in comparison with other food industry sectors

Abstract: Efficiency, as a universal and comprehensive measure of management efficiency, may be referred both to a single enterprise, branch of industry, and the entire economy. The feed industry is a branch of the food industry, which differs greatly from its other sectors. Its specific character results from the generation of products, which are not directly consumed by humans, but are used to feed animals-both pets and farm animals, as a result satisfying human needs. Additionally, enterprises in the feed industry ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The juxtaposition of these industries allowed, at the same time, one to indicate relations between liquidity and profitability in different groups of economic entities (group of enterprises), whose common stakeholder is an agricultural farm (Figure 1). A study by Florek and Czerwi ńska-Kayzer [40] showed that the selected branches in the years studied were not characterized by high variability in their financial situation. Using the TOPSIS method, the analyzed companies had comparable results of financial situation assessment in different years of the studied period.…”
Section: The Data Collectionmentioning
confidence: 88%
“…The juxtaposition of these industries allowed, at the same time, one to indicate relations between liquidity and profitability in different groups of economic entities (group of enterprises), whose common stakeholder is an agricultural farm (Figure 1). A study by Florek and Czerwi ńska-Kayzer [40] showed that the selected branches in the years studied were not characterized by high variability in their financial situation. Using the TOPSIS method, the analyzed companies had comparable results of financial situation assessment in different years of the studied period.…”
Section: The Data Collectionmentioning
confidence: 88%
“…Hence, an analysis was carried out of the financial situation of operators owned by transnational corporations active in the Polish feed market. The financial condition of these undertakings was found to be satisfactory, as reflected by the synthetic indicator of profitability, which was 0.638 in 2015, compared to the average level of 0.585 for the whole Polish food industry [47]. In 1H 2019, animal feed producers recorded a net revenue from product sales of PLN 8.55 billion, i.e., 2.7% more than in 1H 2018.…”
Section: Economic Consequences Of the Globalization Process In The Pomentioning
confidence: 94%